2006
DOI: 10.1359/jbmr.051107
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Fractures in Children After Solid Organ Transplantation: A 5-Year Prospective, Population-Based Study

Abstract: In this population-based prospective follow-up study, children undergoing solid organ transplantation had a highly elevated risk for fractures: The incidence of all fractures was 6-fold higher (92 versus 14 fractures/1000 persons/year; p < 0.001) and vertebral fractures was 160-fold higher (57 versus 0.35 fractures/1000 persons/year; p < 0.001) in the study group compared with the control population. Thus, screening of vertebral fractures at regular intervals is recommended, and preventive strategies should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 39 publications
6
71
4
1
Order By: Relevance
“…Mineral and bone disorder in RTx children may result in decreased bone mineral density (BMD), fractures, bone pain, and growth failure [76,77]. In a cross-sectional study by Valta et al, vertebral fractures were observed in 8 % of RTx children (median age 12 years) and the majority of them were asymptomatic.…”
Section: Bone Healthmentioning
confidence: 99%
“…Mineral and bone disorder in RTx children may result in decreased bone mineral density (BMD), fractures, bone pain, and growth failure [76,77]. In a cross-sectional study by Valta et al, vertebral fractures were observed in 8 % of RTx children (median age 12 years) and the majority of them were asymptomatic.…”
Section: Bone Healthmentioning
confidence: 99%
“…In particular, illnesses associated with chronic inflammation, malabsorption, metabolic disturbances, decreased mobility, or prolonged glucocorticoid therapy may lead to impaired bone health, low BMD, and fractures. (19,20) Primary bone disorders leading to juvenile osteoporosis are relatively rare. The most common of them is osteogenesis imperfecta (OI), caused by mutations in the genes encoding type I collagen.…”
Section: J Jbmrmentioning
confidence: 99%
“…Hip fracture rates among adult dialysis patients undergoing renal transplantation increase even further in the early months following transplantation, then gradually decline [3]. Significantly greater vertebral and extremity fracture rates have also been demonstrated in pediatric solid organ transplant recipients compared with healthy controls: the age-and sex-adjusted hazard ratios for vertebral fractures were 61.3 [95% confidence interval (CI), 40.7-92.4) compared with over 200,000 populationbased controls [4].…”
Section: Introductionmentioning
confidence: 99%